Inovasi dalam Kegiatan Belajar Mengajar dalam Meningkatkan Kualitas Pendidikan di SD Nasima - Kinesti, Rakanita Dyah Ayu; Saputra, Mohammad Aziz; Haqqia, Adiba Hasna Al; Putri, Adinda Anisa; Ananta, Elvara Intan (Darul Yasin Al Sys, 2024)
Innovations implemented at Nasima Elementary School (SD) Semarang to improve learning activities. These innovations include technology integration, relevant curriculum development, interactive teaching methods, and ongoing training for teachers. The aim of implementing this innovation is to create a more dynamic, interesting and effective learning environment so that students can reach their maximum potential. The use of technology such as digital devices and e-learning platforms has enriched students' learning experience and increased their participation. The curriculum is developed based on students' needs and interests through a project-based learning approach which helps in developing critical thinking and teamwork skills. Interactive teaching methods, such as group discussions and simulations, increase student engagement and develop their social skills. Continuous training for teachers ensures increased competence in teaching methods and use of technology. These innovations show how important adaptation is in education to improve the quality of learning at SD Nasima Semarang.